2023
DOI: 10.1007/s40123-023-00679-z
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Effects and Range of Focus in a Multizonal-Refractive Intraocular Lens Compared with a Standard Trifocal Diffractive Design

Abstract: Introduction: This study was performed to compare the optical performance of a multizonal presbyopia-correcting intraocular lens (IOL) and a conventional trifocal model. Methods: The optical quality and simulated visual acuity (VA) of 570 Precizon Presbyopic NVA (OPHTEC BV) and AcrySof IQ PanOptix (Alcon) were compared. The Precizon features a refractive design consisting of alternating optical zones that converge the incident light into two principal foci and a transitional zone for intermediate vision. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, the corrected-distance visual acuities measured with the defocus curve for vergence demands simulating close distances showed a positive correlation with mesopic pupil diameter, indicating that these visual acuities became worse for larger pupil sizes. This is consistent with optical bench studies [1,4] showing almost full pupil independence of the refractive multi-segmented IOL evaluated for photopic pupil sizes, but a slight progressive worsening of the MTF as the mesopic pupil size was larger, especially for the most negative vergence demands (simulating the closest distances). This contrasts with other presbyopia-correcting or EDOF IOLs showing a clearly higher pupil-dependence of the visual outcomes compared to Precizon Presbyopic IOL [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the corrected-distance visual acuities measured with the defocus curve for vergence demands simulating close distances showed a positive correlation with mesopic pupil diameter, indicating that these visual acuities became worse for larger pupil sizes. This is consistent with optical bench studies [1,4] showing almost full pupil independence of the refractive multi-segmented IOL evaluated for photopic pupil sizes, but a slight progressive worsening of the MTF as the mesopic pupil size was larger, especially for the most negative vergence demands (simulating the closest distances). This contrasts with other presbyopia-correcting or EDOF IOLs showing a clearly higher pupil-dependence of the visual outcomes compared to Precizon Presbyopic IOL [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 90%
“…This IOL, with the commercial brand name of Precizon Presbyopic NVA (Ophtec BV, Groningen, The Netherlands), is a multizonal-refractive lens that combines different segments in the optical zone of the IOL providing distance and near vision correction with a smooth transition between them. An experimental study has also demonstrated that this multizonal-refractive IOL has a lower level of decrease in polychromatic optical quality due to material dispersion compared to a widely implanted trifocal diffractive IOL [4]. Some previous clinical studies have shown that the implantation of Precizon Presbyopic IOL is a safe and effective method to provide good visual acuity at all distances in presbyopic and cataract patients [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%